Using Smartphone as a Journalistic Tool: An Examination of Ethical Codes in Mobile Journalism in Saudi Arabia - Ahmed Deen; Po-Lin Pan (Athens Journal of Mass Media and Communications, 2021)
This study aimed to understand the impact of ethical codes on Saudi journalists’ perceptions toward mobile journalism (MOJO). Three major ethical dimensions were examined, including seeking truth, minimizing harm, and being accountable in news coverage. A survey link created with SurveyMonkey was transmitted via social media avenues, such as Twitter and WhatsApp, where Saudi journalists can complete the questionnaire and then share the link with other Saudi journalists. A total of 124 Saudi journalists were recruited by this snowball sampling approach, while the Codes of Ethics of Society of Professional Journalists was adapted as major measurements for three ethical dimensions, including seeking truth, minimizing harm, and being accountable. Results found that all three ethical dimensions of professional journalists generated significant influences on Saudi journalists’ perceptions toward MOJO. Specifically, minimizing harm was found as the most powerful factor that affected Saudi journalists’ perceptions toward MOJO, followed by being accountable and seeking truth, indicating that Saudi journalists who were more likely to seek truth, minimize harm, and be accountable would exhibit more positive perceptions toward MOJO. Although using smartphone as a journalistic tool was a key factor toward Saudi journalists’ MOJO perceptions, it was not as powerful as three ethical dimensions that affected their MOJO perceptions.